Evaluasi Pemekaran Kabupaten Sambas berdasarkan 1 Peraturan Pemerintah Nomor 129 Tahun 2007 - salomo, Roy v.; JANNAH, Lina MIFTAHUL; MUSLIM, MUH. AZIS (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2010)
The year 1999 has been marked as the reform era where the old law on regional autonomy has been replaced with the new ones, i.e. Law Number 22 Year 1999 and Law Number 32 Year 2004. These two new laws have promoted the emergence of new local governments throughout Indonesia, as a process of amalgamation. Between 1999 and 2007 there were 173 new local governments emerged. The assumption that amalgamation will bring more fund and development to the new region (local government) has been the reason why this phenomenon emerged. The Municipality of Sambas is one of the examples. This study has been conducted according to Government Regulation Number 129 Year 2007, to find out whether the Municipality of Sambas was feasible to be amalgamated into three Municipalities. The result of the study shows that based on the indicators stated in Government Regulation Number 129 Year 2007, the amalgamating is not feasible.